Analisis Kinerja Keuangan Perbankan Syariah Menggunakan Metode CAMEL di PT. Bank Tabungan Pensiunan Nasional Syariah Periode 2019-2022 - Sucipto, Moch Cahyo; Zaenal, Rian; Jalaludin, Jalaludin; Nurbaeti, Ayi (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
For banking institutions, the role of financial performance is very important. Because, if the financial performance of a bank has a good predicate, it can directly increase public confidence in making loans or investing. The fluctuating JCI in stock exchange trading certainly affects the stock performances of several issuers, including BTPN Syariah. BTPN Syariah shares have fluctuated from 2019 - 2022. And 38.77% of foreign sales have occurred, so it is very interesting to conduct this research. The purpose of this study was to determine the financial performance of Islamic banking based on the CAMEL (Capital, Asset, Management, Earning and Liquidity) method at PT. Sharia National Pension Savings Bank for the 2019-2022 Period. This study uses a descriptive method with a quantitative approach. Based on the results of the discussion above, it can be concluded that the health level of BTPN Syariah for the 2019-2022 period is based on: 1). Capital (capital) received the title